2004
DOI: 10.1007/s10040-004-0321-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate pollution from agriculture in different hydrogeological zones of the regional groundwater flow system in the North China Plain

Abstract: A survey of the quality of groundwater across a broad area of the North China Plain, undertaken in 1998 to 2000, indicates that nitrate pollution is a serious problem affecting the drinking water for a vast population. The use of nitrogen (N)-fertilizer in agriculture has greatly increased over the past 20 years to meet the food needs of the rapidly expanding population. During the study, 295 water samples were collected from wells and springs to determine the water chemistry and the extent of nitrate pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(60 citation statements)
references
References 12 publications
2
58
0
Order By: Relevance
“…A survey of the NO 3 -N concentrations of shallow groundwater in the North China Plain indicated that approximately 21.5% of the total surface area of the plain had NO 3 -N levels above 10 mg/L (Li et al, 2001). Groundwater NO 3 -N increased significantly as the N fertilization rate increased (Zhao et al, 2007), and the overuse of N fertilizer was the principal factor affecting groundwater nitrate pollution (Chen et al, 2005).…”
Section: Study Areamentioning
confidence: 98%
See 1 more Smart Citation
“…A survey of the NO 3 -N concentrations of shallow groundwater in the North China Plain indicated that approximately 21.5% of the total surface area of the plain had NO 3 -N levels above 10 mg/L (Li et al, 2001). Groundwater NO 3 -N increased significantly as the N fertilization rate increased (Zhao et al, 2007), and the overuse of N fertilizer was the principal factor affecting groundwater nitrate pollution (Chen et al, 2005).…”
Section: Study Areamentioning
confidence: 98%
“…Due to agricultural development and the overuse of N fertilizer, water shortages and water pollution have become very serious problems in the Haihe Basin, which has been one of the most polluted regions in China (Chen et al, 2005;Liu et al, 2010;Wu et al, 2011). A survey of groundwater nitrate-N concentrations in the Haihe Basin showed that approximately 45% of 600 groundwater samples exceeded 11.3 mg NO 3 -N/L (50 mg NO 3 − N/L), the World Health Organization's and Europe's limit for nitrate in drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of surface water with nutrients as well as trace metals and organic xenobiotics has increased in China in the past 30-40 years as a consequence of rapid urbanization, economic growth, intensification of agricultural productivity, and water scarcity [1,2]. Drinking water production requires increasingly laborious and expensive techniques, and surface water ecosystems are under great threat with respect to biodiversity and ambient quality [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Current enhancements in the productivity of the NCP have been driven by two major management changes: the expanded use of inorganic fertilizer since the 1970s, and the increase in irrigation (Li et al, 2011) that enables the harvest of two crops per year. However, the growth in production is taking a toll on the environment, and recent studies report overexploitation of local water resources with observed groundwater (GW) level declines of up to 1 m per year , as well as elevated nitrate concentrations in groundwaters exceeding 11.3 mg NO 3 -N/L (50 mg NO 3 /L), which is the World Health Organization's drinking water standard (Chen et al, 2005;Ju et al, 2006;Zhang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%